Sakaya: Balia Tradition Transformation in The Kaili Tribe Community of Palu, Central Sulawesi - Fakhrurrozi, Hatta; Mashuri, Saepudin; Haeba, Ilham Dwitama; Khoirotun, Ulfun (el Harakah: Jurnal Budaya Islam, 2022)
The social changes of the Palu community after the 2018 disaster affected the values, attitudes, behaviors, and perspectives of some religious groups in society, which in turn forced the Balia tradition to transform as an adaptive step. This qualitative research aims to find the transformation of Balia by using an ethnographic approach. The research location was in the cities of Palu and Sigi. The sample was determined twice using the snowball technique and convenience sampling, which resulted in five respondents. Data was collected using depth interviews and analyzed using triangulation. This study found that Balia has transformed into a new form adapted to the community's needs and demands, called Sakaya. The term Sakaya is intended for someone who can be a medium or a means of communication with supernatural beings. Sakaya is not a colossal ritual but a personal ritual. The transformation occurs in the second aspect of Balia and does not leave the primary aspect. As a result, these rituals have become more effective, efficient, inexpensive, and easily accessible to the public. Another finding of this research is that the function of the Sakaya is extended beyond Balia, which includes economic, social, and political aspects, which makes it more acceptable in the social life of the Kaili tribal community. Perubahan sosial masyarakat Palu pasca bencana 2018 berdampak pada nilai, sikap, perilaku, dan cara pandang sebagian kelompok agama di masyarakat, yang pada gilirannya memaksa tradisi Balia bertransformasi sebagai langkah adaptif. Penelitian kualitatif ini bertujuan untuk menemukan transformasi Balia dengan menggunakan pendekatan etnografi. Lokasi penelitian berada di kota Palu dan Sigi. Penentuan sampel dilakukan sebanyak dua kali dengan teknik snowball dan convenience sampling, yang menghasilkan lima responden. Pengumpulan data dilakukan dengan wawancara mendalam dan dianalisis menggunakan triangulasi. Kajian ini menemukan bahwa Balia telah menjelma menjadi bentuk baru yang telah disesuaikan dengan kebutuhan dan tuntutan masyarakat, yang disebut Sakaya. Istilah Sakaya ditujukan untuk seseorang yang mampu menjadi media atau sarana komunikasi dengan makhluk gaib. Sakaya bukanlah ritual kolosal, melainkan ritual pribadi. Transformasi terjadi pada aspek sekunder Balia dan tidak meninggalkan aspek primer. Alhasil, ritual-ritual tersebut menjadi lebih efektif, efisien, murah, dan mudah dijangkau oleh masyarakat. Temuan lain dari penelitian ini adalah bahwa fungsi Sakaya diperluas di luar Balia, yang meliputi aspek ekonomi, sosial, dan politik, yang membuatnya lebih dapat diterima dalam kehidupan sosial masyarakat suku Kaili.